2020
DOI: 10.1042/cs20201057
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine protects against the development of experimental abdominal aortic aneurysms

Abstract: Abdominal aortic aneurysm (AAA), commonly occurring in the aged population, is a degenerative disease that dilate and weaken infrarenal aorta due to progressive degeneration of aortic wall integrity. Vinpocetine, a derivative of alkaloid vincamine, has long been used for cerebrovascular disorders and cognitive impairment in the aged population. Recent studies have indicated that vinpocetine antagonizes occlusive vascular disorders such as intimal hyperplasia and atherosclerosis. However, its role in vascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Ten‐week‐old wild‐type C57BL/6J male mice were treated with 0.2% 3‐aminopropionitrile fumarate salt (BAPN) (w/v) in drinking water. 12 Periaortic application of porcine pancreas elastase or heat‐deactivated elastase (sham) were blinded performed on infrarenal abdominal aorta as previously described with slight modifications. 12 Mice were treated with vehicle or sildenafil (100‐mg tablets; Viagra, Pfizer) prepared in drinking water to a concentration of 400 mg/L (0.6 mmol/L) as previously described, 13 resulting in the ingestion of ≈60 to 100 mg/kg per day, starting from the seventh day post‐surgery until harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Ten‐week‐old wild‐type C57BL/6J male mice were treated with 0.2% 3‐aminopropionitrile fumarate salt (BAPN) (w/v) in drinking water. 12 Periaortic application of porcine pancreas elastase or heat‐deactivated elastase (sham) were blinded performed on infrarenal abdominal aorta as previously described with slight modifications. 12 Mice were treated with vehicle or sildenafil (100‐mg tablets; Viagra, Pfizer) prepared in drinking water to a concentration of 400 mg/L (0.6 mmol/L) as previously described, 13 resulting in the ingestion of ≈60 to 100 mg/kg per day, starting from the seventh day post‐surgery until harvest.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al. reported that vinpocetine could alleviate AAA development by suppressing TNF-α-induced B cell activation and proinflammatory mediator expression in primary cultured macrophages both in vitro , and in vivo ( 111 ). The interactions of between B cells and other immune cells are illustrated in Figure 2 .…”
Section: Adaptive Immune Cellsmentioning
confidence: 99%
“…These dramatically increasing evidences indicate that B cell may be an ideal target to treat AAA patients, and subsequent experiments confirmed this hypothesis. Zhang et al reported that vinpocetine could alleviate AAA development by suppressing TNF-a-induced B cell activation and proinflammatory mediator expression in primary cultured macrophages both in vitro, and in vivo (111). The interactions of between B cells and other immune cells are illustrated in Figure 2.…”
Section: B Cellsmentioning
confidence: 99%
“…Nuclear translocation was evaluated using NIH ImageJ software with an intensity ratio nuclei cytoplasm macro. Quantification of translocation was expressed as the percentage of intensity in nucleus over total cell (85). The data points shown are from 3 separate experiments with duplicate or triplicate wells.…”
Section: Methodsmentioning
confidence: 99%